Needle Track Seeding of Primary and Secondary Liver Carcinoma After Percutaneous Liver Biopsy - John, Timothy G. (Hindawi Publishing Corporation, 1993)
Seeding of tumour in the needle track following percutaneous needle biopsy of liver neoplasms is rarely reported. We describe two such cases following the needle biopsy of an hepatocellular carcinoma and secondary colorectal carcinoma respectively. The risk of needle track recurrence of liver tumours should not be regarded as insignificant. The diagnosis of liver neoplasms may be achieved by non-invasive modalities, and their needle biopsy should be reserved for cases not amenable to surgical resection.